Women's Rights in National and Civic Education Textbooks for Upper Basic Stage in Jordan (Analytical Study) - alhamaidah, Ola M.; Hdeab, Rasha Y. (Dirasat: Human and Social Sciences, 2024)
Objectives: The study aimed to reveal the women's rights in national and civic education textbooks for upper basic stage, and to identify differences in the inclusion of these rights, according to the grades. Methods: The study used the analytical method (content analysis), the study population and sample consisted of textbooks from the seventh to the tenth grades, for the school year (2018-2019), the researcher prepared a list of content analysis distributed in four domains, validity and reliability indicators have been verified. Results: The results showed that the inclusion of women's rights as a whole ranking in textbooks: seventh grade, ninth grade, tenth grade, and then eighth grade, and that political rights are the most included in the textbook combined, then social rights, followed by economic rights, while family rights came finally. The results also showed a difference in the inclusion of women's rights as a whole, in favor of the seventh and ninth textbooks, and a difference in the inclusion of political rights in favor of the seventh-grade textbooks. Conclusions: The study recommended attention to women's family rights in the four textbooks, and increased inclusion of political rights in the tenth and eighth textbooks, to achieve a balanced matrix of women's rights in the textbooks.